Exploring global food system shocks, scenarios and outcomes. (October 2020) - Hamilton, Hannah; Henry, Roslyn; Rounsevell, Mark; Moran, Dominic; Cossar, Frances; Allen, Kathleen; Boden, Lisa; Alexander, Peter
Highlights: Food system projections need to consider a range of potential shocks scenarios. Connectivity in food systems can increase volatility and vulnerability to shocks. Loss of food system diversity can reduce resilience. Social media is increasingly important in shaping attitudes/ behaviours towards food. Increasing automation within food systems may create new sources of shock. Abstract: Globalised food supply chains are increasingly susceptible to systemic risks, with natural, social and economic shocks in one region potentially leading to price spikes and supply changes experienced at the global scale. Projections commonly extrapolate from recent histories and adopt a 'business as usual' approach that risks failing to take account of shocks or unpredictable events that can have dramatic consequences for the status quo, as seen with the global Covid-19 pandemic. This study used an explorative stakeholder process and shock centred narratives to discuss the potential impact of a diversity of shocks, examining system characteristics and trends that may amplify their impact. Through the development of scenarios, stakeholders revealed concerns about the stability of the food system and the social, economic and environmental consequence of food related shocks. Increasing connectivity served as a mechanism to heighten volatility and vulnerability within all scenarios, with reliance on singular crops and technologies (i.e. low diversity) throughout systems highlighted as another potential source of vulnerability. The growing role of social media in shaping attitudes and behaviours towards food, and the increasing role of automation emerged as contemporary areas of concern, which have thus far been little explored within the literature.